Puncturing effects on turbo codes - Kousa, M.A. (2002)
The authors address various important issues related to punctured turbo codes. A modified technique for finding the transfer function of punctured turbo codes is developed. This modified technique provides a means of deterministic evaluation of the weight distribution of the code, as well as a possibility of studying various puncturing patterns. These advantages are shown with some illustrative examples. Moreover, the paper explains some characteristics of the puncturing pattern, and arrives at useful guidelines for the design of a good puncturing matrix